Neoplasia and Proliferative Lesions of New World Camelids: A Systematic Literature Review and Retrospective Study of Cases Submitted to Colorado State University From 1995 to 2020 - Aboellail, Tawfik A.; Waugh, Max; Harvey, Alexandra; Fisher, Jade; Vilander, Allison C. (Frontiers in Veterinary Science, 2021)
Camelid pathology submissions to veterinary diagnostic laboratories are on the rise given the increasing popularity and population of llamas and alpacas especially in the western United States. When compared to other animals, the field of camelid neoplasia has a relative paucity of cases reported in the literature. The Colorado State University Veterinary Diagnostic Laboratories (CSU-VDL) has had a steady increase in the numbers of camelid pathology submissions allowing for a robust review of diagnoses of neoplasia in new world camelids. Here we present a retrospective analysis of camelid neoplastic and proliferative lesions diagnosed at the CSU-VDL from 1995-2020, followed by an extensive literature review. Results show increasing incidence of camelid neoplasia reported in the literature therefore becoming a common diagnosis in llamas and alpacas. Proliferative and neoplastic lesions were diagnosed in 8.8% of new world camelid submissions to CSU-VDL with the most common tumors being lymphomas, squamous cell carcinomas, fibromas, and adenocarcinomas. Risk factors are female sex and increased age except in the case of lymphoma, which tends to occur in younger camelids. Lymphomas, melanomas, and adenocarcinomas (especially of gastrointestinal tract) carry an increased risk of multiple organ system involvement often with widespread metastases. Conditions described in camelids for the first time include osteosarcoma, cutaneous hemangiosarcoma, myxosarcoma, pilomatricoma, ovarian theca cell tumor, congenital nevus with malignant transformation, and various other neoplasia. This article will provide an operational guide for camelid neoplasia to further assist veterinary laboratory diagnosticians, researchers and practicing veterinarians in the field of camelid medicine and pathology.